Sosialisasi Tote Bag Bermotif Eco Print Sebagai Alternatif Pengganti Tas Plastik - M. Alfani Rinaldi; Afifah Kamilatul Unsha; Alayda Adyatami; Ni Made Ayu Alya Putri Kumara; Ginanjar Wisnu Alparizi; Muhammad Amrullah Azhari; Kalsum Hidayati; Novia Zantika Safitri; Mila Silvira Syafna; Wardiatul Husni; Ida Ayu Oka Suwati Sideman (CV. Multi Kreasi Media, 2025)
The use of plastic bags is a common problem as a form of practical packaging activities, especially during commercial or trading activities. These single-use plastic bags are a waste-forming material that is difficult to decompose and has a significantly increasing volume and is global. Plastic bag waste is not only a problem for land pollution, but also for water bodies, so in addition to setting high prices for plastic bags, the use of cloth tote bags is a suitable alternative. Unfortunately, the use of chemical dyes to enhance the aesthetic value of cloth tote bags has caused problems with water bodies pollution. One solution offered is to use eco-print techniques from natural materials as motifs to beautify the appearance of tote bags. To this end, an activity